TRADISI MBERE BESI MERSIK PENYERAHAN TUMBUK LADA PADA ETNIS KARO DI DESA MBETUNG KECAMATAN JUHAR - Tarigan, Lisentia Adriana; Amal, Bakhrul Khai (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Mbere besi mersik it is a Tradition that is believed to be a tradition that aims to strengthen a person ‘s spirit or soul. From here it became known to the community and now because it has a big impact on those who practice this tradition, for the community Mbetung, here it can be a solution related to problems such as poor health, disharmonius household, married but without the blessing of their parents. And haven’t tried it yet. partner this can be overcome by carrying out the tradition of clean revision by the community Mbetung.There are several kinds of values and symbols contained in the mersik iron Mbere tradition, research was carried out with the aim of describing what values and symbols are contained in the mersik iron Mbere tradition which has a huge impact on the lives of the people in Mbetung Village. The research method is using qualitative research with a descriptive approach where data is collected through field observations, in-depth interviews with 11 informants, and documentation. The results of the research explain what the symbolic values and importance of the mersik iron mbere tradition are and what impacts are experienced by the people of Mbetung village, Juhar subdistrict. The traditional values of the mersik iron mbere are an introspective attitude, the value of respecting ancestors, the value of a humble attitude, this tradition is carried out based on the Karo calendar which functions to see good days as a belief in the smooth running of the event that will be held, as for the location of the tardisi ino at home. bere, namely those who experience pain or irregularities